(untitled) (Research, Society and Development, 2022)
In this paper we present the results of a research that analyzed a Mathematics class planned with games, for students of the 7th year of Elementary School, which originated from the following questions: What the teacher and the students do, in fact, in mathematics classes planned by means of games and what categories describe their actions? What connections can be made between teacher and student actions in such classes? The methodological procedures were based on Content Analysis. Emerged from the analyzes eighteen categories of teacher actions and fifteen of student actions. Regarding the possible connections between the teacher actions and the student actions the results indicated that in classes planned with games the actions carried out by the teacher present, in some moments, connections with the actions carried out by the students. But the connection does not imply causality, that is, a certain teacher action does not necessarily condition, induce or originate certain student action.